Developing an Anti-Tumor Therapy: Expression of mLIGHT Cytokine in Escherichia coli & Salmonella enterica Typhimurium - Ton, Angie (My University, 2012)
Current conventional cancer treatments such as chemotherapy and radiation have many limitations and adverse side effects. Salmonella enterica Typhimurium has been shown to colonize solid tumors, making this bacterium a potentially useful vector for delivering cytokines that promote tumor rejection. The objective of this project is to express mouse LIGHT (mLIGHT) cytokine, a tumor necrosis factor that promotes apoptosis, as a secreted protein in first E. coli and then S. enterica. Like S. enterica, E. coli is a Gram-negative facultative anaerobe, but can be used in a Biosafety Level 1 labtoratory. Soluble proteins, insoluble proteins, and secreted proteins were isolated from E. coli cultures harboring expression vectors that contain mLIGHT cDNA and the hemolysin secretion signal sequence under the control of the Trc promoter. Western blotting indicated that mLIGHT is expressed as an insoluble protein, but not as a soluble or secreted protein. These findings suggest that other promoters and secretion signal sequences need to be tested to express mLIGHT as a secreted protein. Once a construct is made that results in expression of mLIGHT as a secreted protein in E. coli, the construct will be introduced into S. enterica. The bacterium will eventually be evaluated for its effectiveness as an anti-tumor therapy in mouse models of solid tumors.
Faculty adviser: Dr. Janet Schottel
Keywords: College of Biological Sciences; Department of Biochemistry, Molecular Biology, and Biophysics